Data Link Layer Encryption for The Internet of Things Using Elliptic Curve Cryptography Over Visible Light Communication Channel - Ene, D; Anireh, V.I.E; Matthias, D (International Journal of Computer Sciences and Engineering, 2020)
The Internet as a fast-growing communication infrastructure comes with additional challenges of cybersecurity. A few techniques have been created to provide security in the application, transport, or network layer of a network. Many organizations have worked to provide security at higher OSI layers, from application layer right down to the network layers, without any at the Data Link layer. This has opened up many systems to a variety of compromises and attacks. This study proposes the provision of the public key Elliptic Curve Cryptography to serve the Data Link Layer instead of the Media Access Control (MAC). In this study, visible light communication technology for fast data communication and secure data transmission on the data link layer using public-key cryptosystem are discussed. The visible light communication technology consists of Light Emitting Diodes (LED) that flicker at an incredibly high frequency, thereby enabling a very high-speed wireless communication and an elliptic curve encryption component that carries out an integrated encryption scheme using Elliptic Curve Integrated Encryption Scheme (ECIES) and a digital signature algorithm using Elliptic Curve Digital Signature Algorithm (ECDSA). For the data link layer security, the encryption procedure is applied to the communications server and the programmable circuit boards (PCB) controlling the visible light communication devices. While the complete system model was implemented in a program, a prototype of the architecture was implemented on a microFourQ-MSP-IAR Embedded Workbench IDE-MSP430 7.12.4, and Wolfram Mathematica. Two advantages of visible light communication and public-key encryption were demonstrated: 1) providing security for the data link layer messages. 2) using VLC to speed up the encryption and decryption process in the data link layer.